1998
DOI: 10.1093/emboj/17.18.5349
|View full text |Cite
|
Sign up to set email alerts
|

Evidence implicating Gfi-1 and Pim-1 in pre-T-cell differentiation steps associated with β-selection

Abstract: After rearrangement of the T-cell receptor (TCR)β-locus, early CD4 -/CD8 -double negative (DN) thymic T-cells undergo a process termed 'β-selection' that allows the preferential expansion of cells with a functional TCR β-chain. This process leads to the formation of a rapidly cycling subset of DN cells that subsequently develop into CD4 ϩ /CD8 ϩ double positive (DP) cells. Using transgenic mice that constitutively express the zinc finger protein Gfi-1 and the serine/threonine kinase Pim-1, we found that the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 37 publications
(66 reference statements)
4
71
0
Order By: Relevance
“…Induction of Gfi-1 by IL-4 increases Th2 cell expansion by promoting proliferation and preventing apoptosis (10). Gfi-1 cooperates with the cell-cycle regulators PIM-1 and cMyc (6,7,40). The E2F family of transcription factors also plays a critical role in cell-cycle progression through its ability to regulate the expression of target genes, including cyclins and cyclin-dependent kinases (41).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of Gfi-1 by IL-4 increases Th2 cell expansion by promoting proliferation and preventing apoptosis (10). Gfi-1 cooperates with the cell-cycle regulators PIM-1 and cMyc (6,7,40). The E2F family of transcription factors also plays a critical role in cell-cycle progression through its ability to regulate the expression of target genes, including cyclins and cyclin-dependent kinases (41).…”
Section: Discussionmentioning
confidence: 99%
“…Among these are Socs-1, which functions at the transition from the CD25 þ CD44 À double-negative thymocyte stage to the CD4 þ CD8 þ double-positive stage stage (Fujimoto et al, 2000;Trop et al, 2001), and the oncogenic Tcell transcription factor Gfi-1 (Schmidt et al, 1998a), which is similarly required at this stage (Schmidt et al, 1998b) and which has been reported to predispose to Tcell tumorigenesis by promoting S-phase entry concomitant with hyperphosphorylation of Rb (Karsunky et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Both Pim-1 and Pim-2 have been implicated in thymocyte development (17,27). Forced expression of Pim-1 rescues the defects in thymocyte development caused by deficiency in RAG, IL-7, or the common ␥-chain of cytokine receptors (17).…”
Section: Discussionmentioning
confidence: 99%